2005
DOI: 10.1111/j.1582-4934.2005.tb00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal disease models generated by genetic engineering of polyamine metabolism

Abstract: The natural polyamines (putrescine, spermidine and spermine) are aliphatic amines containing two (putrescine), three (spermidine) or four (spermine) primary or secondary amino groups. At physiological pH values, these amino groups are positively charged and hence the polyamines AbstractThe polyamines putrescine, spermidine and spermine are natural components of all living cells. Although their exact cellular functions are still largely unknown, a constant supply of these compounds is required for mammalian ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 88 publications
(130 reference statements)
0
35
0
Order By: Relevance
“…In humans, the concentration in CSF of spermine is greater than that of other polyamines, such as putrescine and spermidine, 36) although the whole blood concentration of spermine is similar to that of spermidine. 37) Since spermine is the end-product of polyamine bio-synthesis, [6][7][8] it is considered that this carrier-mediated spermine efflux transport at the BCSFB takes part in the modulation of polyamine concentrations in the brain. Therefore, this finding will help in our understanding of neural concentration homeostasis of polyamines, including spermine, and thus modulation of neuro-exciting signal transduction via spermine-related Nmethyl-D-aspartate pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the concentration in CSF of spermine is greater than that of other polyamines, such as putrescine and spermidine, 36) although the whole blood concentration of spermine is similar to that of spermidine. 37) Since spermine is the end-product of polyamine bio-synthesis, [6][7][8] it is considered that this carrier-mediated spermine efflux transport at the BCSFB takes part in the modulation of polyamine concentrations in the brain. Therefore, this finding will help in our understanding of neural concentration homeostasis of polyamines, including spermine, and thus modulation of neuro-exciting signal transduction via spermine-related Nmethyl-D-aspartate pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The precursor of spermine is spermidine, 5) which is synthesized from putrescine and it has been reported that the biosynthesis of spermine from spermidine is superior to that of spermidine from spermine. [6][7][8] Hence, neural spermine transport system(s) could be important for the removal of spermine from the brain, and the modulation of cerebral spermine concentration.…”
mentioning
confidence: 99%
“…Polyamines are strongly associated with cell proliferation, up-regulated in many cancers, and essential for liver regeneration, so circadian regulation of this pathway may gate the hepatocyte's permissibility to initiate liver regeneration (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Putrescine [4], spermidine [34], and spermine [343] are polyamines commonly observed in the cells of various living organisms, from viruses to humans (1)(2)(3)(4). Polyamines are important in cell proliferation and cell differentiation (5,6), as well as contributing to adaptation to various stresses (7). Interestingly, in addition to common polyamines, thermophiles contain two types of unusual polyamines as major polyamines.…”
mentioning
confidence: 99%